Metadata record for: A global database of Holocene paleotemperature records - Scientific Data Curation Team (2020)
This dataset contains key characteristics about the data described in the Data Descriptor A global database of Holocene paleotemperature records. Contents: 1. human readable metadata summary table in CSV format 2. machine readable metadata file in JSON format
Artwork Size: 3602 Bytes Pages: 3602 Bytes